Development and evaluation of an educational training package to promote health and wellbeing - Gartshore, Emily; Briggs, Lydia; Blake, Holly (Mark Allen Healthcare, 2017)
Background: Supporting the health and wellbeing of healthcare employees is a UK national priority. Aims: To design, deliver and evaluate an educational package to promote health and wellbeing for nurses and midwives Methods: An online training package was developed and administered in two ways: online (HAWN-online) or in a face-to-face workshop (HAWN-contact). A mixed- methods evaluation was used to assess usability and acceptability of HAWN training. Findings: 316 nurses, midwives and students completed the online training package. 16 participants attended the workshop. HAWN-online significantly increased knowledge in core areas of workplace health and wellbeing. Nurses and midwives valued online and face-to-face delivery but raised barriers to attendance at workshops. Participants advocated that training in workplace health should be mandatory for all frontline staff. Conclusions: Employers should take steps to promote staff wellbeing through HAWN training, and address barriers to accessing workplace health training or supportive services.